2014
DOI: 10.1002/zaac.201300669
|View full text |Cite
|
Sign up to set email alerts
|

Structure and Properties of New Gallium‐containing Polyoxotungstates with Hexanuclear and Tetranuclear Cores

Abstract: A series of new gallium‐containing silicotungstates was obtained from the one step reaction of the lacunary Na10[α‐SiW9O34]·15H2O Keggin‐type building block (SiW9) with gallium nitrate in aqueous solution. The sandwich‐type polyoxotungstate [Ga6(H2O)x{α‐SiW9O34(OH)y}2]n– (1) crystallizes first as a mixture of two similar polyoxometalates (1a and 1b), while [Ga4(H2O)2{α‐SiW10O38}2]12– (2) is generated from the mother liquor in a second step. Both newly obtained polyoxometalates with tetra‐ and hexanuclear galli… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
9
0

Year Published

2014
2014
2018
2018

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 11 publications
(10 citation statements)
references
References 64 publications
(2 reference statements)
1
9
0
Order By: Relevance
“…Synthetic and structural studies of group 13 ion-containing POMs provide informative and definitive molecular models of group 13 metal clusters in solution. However, among all the Al-, Ga-, and In-containing POMs, formed by the substitution of several tungsten ions in the parent POMs with trivalent group 13 ions [28,[33][34][35][36][37][38][39][40], few well-characterized In-containing POMs have been reported to date [41][42][43]. Thus, In-containing POMs are intriguing target compounds from both a synthetic and a structural point of view.…”
Section: Introductionmentioning
confidence: 99%
“…Synthetic and structural studies of group 13 ion-containing POMs provide informative and definitive molecular models of group 13 metal clusters in solution. However, among all the Al-, Ga-, and In-containing POMs, formed by the substitution of several tungsten ions in the parent POMs with trivalent group 13 ions [28,[33][34][35][36][37][38][39][40], few well-characterized In-containing POMs have been reported to date [41][42][43]. Thus, In-containing POMs are intriguing target compounds from both a synthetic and a structural point of view.…”
Section: Introductionmentioning
confidence: 99%
“…Bond valence sum (BVS) calculations11 suggested that the oxygen atoms (O67, O68, O69, O70, O71, and O72) are protonated (the BVS value; O67, 1.111; O68, 1.116; O69, 1.111; O70, 0.995; O71, 1.024; O72, 1.083; Table S2, Supporting Information). In contrast, it should be noted that Patzke 's group reported that the corner‐ and edge‐sharing oxygen atoms connecting to neighboring gallium atoms were di‐protonated, i.e., [{Ga 4 (H 2 O) 6 }Si 2 W 18 O 66 ] n – 6e. Each Ga atom is bonded to three oxygen atoms of the lacunary site in the open‐Dawson polyanion, [α,α‐Si 2 W 18 O 66 ] 16– [Ga–O average 2.014 Å].…”
Section: Resultsmentioning
confidence: 98%
“…The reaction condition of Ga 4 ‐ open was similar to that of Al 4 ‐ open with the exception of the metal source, Ga(NO 3 ) 3 · n H 2 O instead of Al(NO 3 ) 3 · 9H 2 O, and the counter cations of the precursor of trilacunary Keggin POM, i.e., K + vs. Na + . Patzke's group has previously obtained Ga 4 ‐ open only as a by‐product of the trigallium(III)‐substituted dimer, [Ga 6 (H 2 O) x {α‐SiW 9 O 34 (OH) y } 2 ] n – ( Ga 6 ‐ dimer ) and the di‐gallium(III) substituted dimer, [Ga 4 (H 2 O) 2 {α‐SiW 10 O 38 } 2 ] 12– ( Ga 4 ‐ dimer ) 6e. By using their synthetic method, Ga 4 ‐ open was not isolated as main product.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations